Modern Technologies and Disability – Between the Promise of Empowerment and the Risk of Exclusion (Inclusive Digital Technologies: Perspectives, Opportunities, and Limitations, 2025)
In the era of rapid digital technology development, the issue of accessibility and inclusion is gainingparticular importance. Technological solutions, though theoretically neutral, can in practice reinforceexisting social divisions—unless they are designed in a consciously inclusive way. On the onehand, these technologies ofer new opportunities for independence, participation, and educationfor people with disabilities. On the other, if they ignore the needs of these users, they become yetanother source of barriers.Tis calls for a deeper refection on the role and signifcance of modern technologies in relationto people with disabilities.Tis chapter serves as an introduction to the monograph, in which individual chapters discussvarious aspects of technological and social inclusion.